Preparation of Zr4+ doped calcium hexaaluminate with improved slag penetration resistance. Issue 9 (10th May 2021) - Guo, Chunyu; Wang, Enhui; Hou, Xinmei; Kang, Junyi; Yang, Tao; Liang, Tongxiang; Bei, Guoping
Abstract: Aiming to improve the density of calcium hexaaluminate (CA6 ), Zr 4+ doped CA6 with the structural formula of CaAl11.73 ◊0.25 Zr0.02 O18.41 ◊0 . 59 (CaAl11.73 Zr0.02 O18.41 ) was successfully synthesized at 1600℃ for 4 h in air. The effect of Zr 4+ doping on the crystal structure of CA6 was investigated using first principle calculation, structure refinement in combination with experimental characterization. The results suggest that Zr 4+ prefers to substitute the Al 3+ at Al3 site, which can increase the lattice parameter of c ‐axis and the amount of Al vacancies. The average thickness of Zr 4+ doped CA6 is increased by approximate 36% in comparison with the pure one. In addition, molecular dynamics (MD) simulation indicates that Zr 4+ doping can reduce the wettability of CA6 to slag to some extent. The reaction test method was carried out and it shows that CA6 with Zr 4+ doping possesses better slag penetration resistance. Based on this, the reaction mechanism is also discussed.